The Supernova – ISM/Star-formation interplay. Issue Volume 9:Issue S296(2013) (29th January 2014) - Hensler, Gerhard
Abstract: Supernovae are the most energetic stellar events and influence the interstellar medium by their gasdynamics and energetics. By this, both also affect the star formation positively and negatively. In this paper, we review the complexity of investigations aiming at understanding the interchange between supernova explosions with the star-forming molecular clouds. Commencing from analytical studies the paper advances to numerical models of supernova feedback from superbubble scales to galaxy structure. We also discuss parametrizations of star-formation and supernova-energy transfer efficiencies. Since evolutionary models from the interstellar medium to galaxies are numerous and are applying multiple recipes of these parameters, only a representative selection of studies can be discussed here.